Controlling the pyridinium–zwitterionic ligand ratio on atomically precise gold nanoclusters allowing for eradicating Gram-positive drug-resistant bacteria and retaining biocompatibility. Issue 44 (3rd November 2021) - Pang, Zeyang; Li, Qizhen; Jia, Yuexiao; Yan, Weixiao; Qi, Jie; Guo, Yuan; Hu, Fupin; Zhou, Dejian; Jiang, Xingyu
Abstract : A NIR-II fluorescent Au25 nanocluster capped with optimal dual functional ligands can effectively aggregate and kill Gram-positive drug-resistant bacteria while maintaining good biocompatibility. Abstract : Infections caused by multidrug-resistant (MDR) bacteria are an increasing global healthcare concern. In this study, we developed a dual-ligand-functionalised Au25 (SR1 ) x (SR2 )18− x -type gold nanocluster and determined its antibacterial activity against MDR bacterial strains. The pyridinium ligand (SR1 ) provided bactericidal potency and the zwitterionic ligand (SR2 ) enhanced the stability and biocompatibility. By optimising the ligand ratio, our gold nanocluster could effectively kill MDR Gram-positive bacteria via multiple antibacterial actions, including inducing bacterial aggregation, disrupting bacterial membrane integrity and potential, and generating reactive oxygen species. Moreover, combining the optimised gold nanocluster with common antibiotics could significantly enhance the antibacterial activity against MDR bacteria both in in vitro and animal models of skin infections. Furthermore, the fluorescence of the gold nanocluster at the second near-infrared (NIR-II) biological window allowed for the monitoring of its biodistribution and body clearance, which confirmed that the gold nanoclusters had good renal clearance and biocompatibility. This study provides a new strategy to combat the MDR challenge using multifunctional gold nanomaterials.